Hydride transfer versus H‐abstraction in the reaction of O3 with 2‐propanol: The influence of solvent. (22nd September 2021) - Reisz, Erika; Naumov, Sergej; Tekle‐Röttering, Agnes; Schmidt, Winfried
Abstract: The main purpose of this paper was to systematically investigate the influence of the solvent on mechanism behind O3 reaction with 2‐propanol. Gibbs energies were calculated for the reactions that initiated the possible mechanisms: hydride transfer ((H3 C)2 (HO)C–H(solv) + O3(solv) → (H3 C)2 (HO)C + (solv) + HO3 − (solv) ) and H‐abstraction ((H3 C)2 (HO)C–H(solv) + O3(solv) → (H3 C)2 (HO)C(solv) + HO3 (solv) ) under working conditions with various solvents. The characteristic of the solvent used for calculations was the relative dielectric constant, ɛ, which ranged from 2.02 (cyclohexane) to 80 (water). The calculation method was based on density functional theory (DFT). In addition, this study took into consideration the conversion of the radical pair as products of H‐abstraction to the ion pair formed following hydride transfer; the conversion occurred by electron transfer ((H3 C)2 (HO)C(solv) + HO3 (solv) → (H3 C)2 (HO)C + (solv) + HO3 − (solv) ). Our calculations showed that the reaction of O3 with 2‐propanol was triggered by H‐abstraction in nonpolar solvents, but in polar solvents, mainly by a pseudo‐hydride transfer consisting of H‐abstraction followed by electron transfer between the radicals formed by H‐abstraction. The transition state formed en route to products had a linear structure for water, whereas for cyclohexane, linear and cyclic transition states coexisted. Abstract : This paper systematically investigated the influence of the solvent on mechanism behind O3 reaction with 2‐propanol. Thus, in non‐polar solvents (low dielectric constants), the reaction was triggered by H‐abstraction, but in polar solvents, by a pseudo‐hydride transfer involving concerted two‐step reactions, that is, H‐abstraction followed by electron transfer between the radicals formed in the first step.